1990
DOI: 10.1085/jgp.95.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ channels from the sea urchin sperm plasma membrane.

Abstract: Ca ~+ influx across the sea urchin sperm plasma membrane is a necessary step during the egg jelly-induced acrosome reaction. There is pharmacological evidence for the involvement of Ca 2+ channels in this influx, but their presence has not been directly demonstrated because of the small size of this cell. Sea urchin sperm Ca 2+ channels are being studied by fusing isolated plasma membranes into planar lipid brayers. With this strategy, a Ca P+ channel has been detected with the following characteristics: (a) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…The channel poorly discriminated for divalent over monovalent cations (P Ca /P Na ϭ 6). La 3ϩ , Co 2ϩ , and Cd 2ϩ which inhibit the EJ-induced AR at millimolar concentrations blocked the channel with a similar potency (325). These findings suggested that this channel could participate in the AR (325).…”
Section: -Permeable and Voltage-dependent Channelmentioning
confidence: 75%
“…The channel poorly discriminated for divalent over monovalent cations (P Ca /P Na ϭ 6). La 3ϩ , Co 2ϩ , and Cd 2ϩ which inhibit the EJ-induced AR at millimolar concentrations blocked the channel with a similar potency (325). These findings suggested that this channel could participate in the AR (325).…”
Section: -Permeable and Voltage-dependent Channelmentioning
confidence: 75%
“…Notably, a high-conductance, Ca 2þ -permeable channel, whose properties resemble some of those displayed by the PC1-PC2 channels, has been recorded in BLMs containing sea urchin or mouse sperm plasma membranes (Lievano et al 1990, Beltran et al 1994. The sea urchin sperm channel discriminates poorly between monovalent and divalent cations (PCa/PNa , 5; Lievano et al 1990). This evidence suggests that REJ and PC proteins may be involved in the ion fluxes that follow binding of FSP and lead to the AR.…”
Section: Acrosome Reaction In Marine Spermmentioning
confidence: 97%
“…Indeed, sea urchin sperm possess a PC2 homolog (suPC2) associated with suREJ3 in the sperm plasma membrane in a thin band overlying the acrosomal vesicle (Mengerink et al 2002, Neill & Vacquier 2004. Notably, a high-conductance, Ca 2þ -permeable channel, whose properties resemble some of those displayed by the PC1-PC2 channels, has been recorded in BLMs containing sea urchin or mouse sperm plasma membranes (Lievano et al 1990, Beltran et al 1994. The sea urchin sperm channel discriminates poorly between monovalent and divalent cations (PCa/PNa , 5; Lievano et al 1990).…”
Section: Acrosome Reaction In Marine Spermmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma membrane of spermatogonial cells is functionally and structurally similar to the membrane of mature sperm, but there are many differences in types and cell distribution of ion channels (Serrano et al, 1999). The third alternative is the reconstitution of ion channels in artificial lipid bilayers; however, this technique removes the ion-channels from their natural lipidic environment and therefore, their biophysical properties are not precisely the same as in the cell plasma membrane (Lievano et al, 1990). The probability of obtaining a high resistance seal of the sperm head by microscopy using perforated patch clamp is about 45%; this is 15 times greater than the probability reported in studies using conventional "patch-clamp".…”
Section: The Sperm Cell Patch-clampmentioning
confidence: 99%